Effect of farm machinery adoption on household income and food security: evidence from a nationwide household survey in India - Jena, Pradyot Ranjan; Tanti, Purna C. (Frontiers in Sustainable Food Systems, 2023)
An increase in farm productivity and income is crucially linked to farm mechanization. Labour shortage in rural areas and frequent extreme weather events have made a resounding pitch for the deepening of farm mechanization in India. Our study examines the effect of agricultural machinery adoption on net agricultural income, household income, and household consumption in India; the latter is considered an indicator of food security. A nationwide household survey of 10253 households drawn from the majority of states of India has been used. Of the three types of machinery investigated, such as tractors, electric pumps, and diesel pumps, the average adoption rates are found to be low in the country, i.e., 8% for tractors, 24% for electric pumps, and 14% for diesel pumps. The wide heterogeneity in terms of adoption is mostly rooted in the large geographical differences among the states of India, as machinery adoption is concentrated in the north and north-central plains of the country. To assess the impact of machinery adoption on the outcome variables, the endogenous switching regression (ESR) model is used. The first stage of ESR, which is a probit model, reveals the determinants of mechanization as access to credit, climatic shocks, access to irrigation, and farmer cooperative membership. The average treatment effect estimates from the second stage outcome regression reveal that the adoption of machinery has increased net agricultural income by 31%, household income by 19%, and food consumption by 5%. Given these demonstrable positive effects of mechanization in agriculture, there is a need for deepening of low-cost scale appropriate farm machines suitable for smallholders. Government support would play a pivotal role in this direction by making farm credits accessible to smallholders, providing timely subsidies on machinery purchase, and providing required extension services.